2011
DOI: 10.1007/s00424-010-0910-5
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: decoding the microRNA response to hypoxia

Abstract: microRNAs (miRNAs) were discovered nearly two decades ago by researchers who sought to understand how basic developmental mechanisms work in the nematode Caenorhabditis elegans. Since the identification of conserved miRNA families in higher eukaryotes, there has been an explosion of interest into how these tiny RNA molecules function. miRNAs are 20-24 nucleotide non-coding RNA molecules that predominantly regulate transcripts of target genes through translational inhibition. Much recent interest has focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 83 publications
(115 reference statements)
1
63
0
Order By: Relevance
“…For example, the ability to sense and respond to hypoxia is of fundamental importance to aerobic organisms, whereas dysregulated oxygen homeostasis is a hallmark in the pathophysiology of cancer, neurological dysfunction, myocardial infarction, and lung disease [17]. Since 2006, a multitude of reports have demonstrated that specific miRNAs are involved in hypoxic response and contribute to the repression of biologically important genes by low oxygen tension from a variety of different organisms, cell types, and disease states [1821].…”
Section: Mirnas and Alterations Of Their Expression In Response To MImentioning
confidence: 99%
“…For example, the ability to sense and respond to hypoxia is of fundamental importance to aerobic organisms, whereas dysregulated oxygen homeostasis is a hallmark in the pathophysiology of cancer, neurological dysfunction, myocardial infarction, and lung disease [17]. Since 2006, a multitude of reports have demonstrated that specific miRNAs are involved in hypoxic response and contribute to the repression of biologically important genes by low oxygen tension from a variety of different organisms, cell types, and disease states [1821].…”
Section: Mirnas and Alterations Of Their Expression In Response To MImentioning
confidence: 99%
“…Hypoxia inducible factor-1α (HIF-1α) (13-18) is a transcription factor that is crucial for normal brain development and in the development of injuries. MicroRNAs (miRs), small (18-25 nts), non-coding RNAs that regulate gene expression by blocking the translation of target mRNAs or by accelerating their degradation, have recently been reported to be induced by hypoxia (19). In particular, miR-210, which is activated by HIF-1α (20), is a unique miR that has been evolutionarily conserved and ubiquitously expressed in hypoxic cell and tissue types (21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…elegans has evolved the ability to survive low-oxygen environments and has therefore been utilized as a genetic model system to understand molecular responses to oxygen deprivation (Gray et al 2004;Powell-Coffman 2010;Padilla et al 2011;Pocock 2011;Ma et al 2013). C. elegans survive severe oxygen deprivation (1 day of anoxia, ,0.001 kPa O 2 , standard OP50 Escherichia coli diet, 20°) by entering into a hypometabolic state referred to as suspended animation.…”
mentioning
confidence: 99%